Omission of adjuvant radiotherapy for older adults with early-stage breast cancer particularly in the COVID era: A literature review (on the behalf of Italian Association of Radiotherapy and Clinical Oncology). Issue 7 (September 2021) - Palumbo, Isabella; Borghesi, Simona; Gregucci, Fabiana; Falivene, Sara; Fontana, Antonella; Aristei, Cynthia; Ciabattoni, Antonella
Abstract: This review is aimed at evaluating whether radiation therapy (RT) can be omitted in older adult early-stage low-risk breast cancer (BC) patients. The published data are particularly relevant at present, during the COVID-19 pandemic emergency, to define a treatment strategy and to prioritize essential therapy. Cochrane Database of Systematic Reviews and PubMED were systematically researched from outset through April 2020 using Mesh terms. Only randomized controlled trials (RCT), with one arm without adjuvant whole-breast irradiation (WBI), were included in the analysis. Recent literature regarding the COVID pandemic and BC RT was assessed. The reported RCTs identified a group of BC patients (pT1-2N0M0 R0, grade 1–2, estrogen receptor (ER) positive, human epidermal growth factor receptor 2 (HER2) negative tumours) in which the absolute risk of local recurrence (LR) was considered low enough to omit RT. The most common risk factors were tumor diameter, nodal and receptor status. Adjuvant RT had a significant impact on LR but not on distant metastasis (DM) or death. During the COVID 19 pandemic, results from RTCs were re-considered to define treatment recommendations for BC patients. International scientific societies and radiation oncology experts suggested RT omission, whenever possible, in older adult early-stage BC patients. Adjuvant RT might be omitted in a highly selected group of older adult early-stage BC patients with favourable prognostic factors. Hypofractionated regimens should be the standard. RT omission, partial breast irradiation (PBI), and ultra- hypofractionated regimens could be considered in selected cases due to the pandemic.